Ice Bridges on the St. Lawrence River as an Index of Winter Severity from 1620 to 1910 - Houle, Daniel; Moore, Jean-David; Provencher, Jean (Journal of Climate, 2007)
Keywords: Climat

Climate Change Adaptation and Mitigation through Urban Agriculture: A Montreal Case Study - Lebedeva, Julia (Université McGill, 2008)
Keywords: Climat

La prise en compte de l’adaptation au changement climatique dans les politiques publiques de verdissement (2005-2015) : le cas de Montréal - Vachon, Jérémie (Université de Montréal, 2016)
Keywords: Climat

Enjeux et dynamiques de la mise en œuvre de stratégies d'adaptation aux changements climatiques en milieu urbain: les cas de Montréal et Paris - Simonet, Guillaume (Université du Québec à Montréal, 2011)
Keywords: Climat

Recherche ou lobbyisme ? L’Institut économique de Montréal et le réchauffement climatique depuis 1999 - Lamy, Guillaume (Politique et Sociétés, 2022)
Keywords: Climat; Libéralisme

A Change in Climate: The Conquest and the Marchands of Montreal - Igartua, José (Viewpoints: Readings in Canadian History, 2006)
Keywords: Fourrure; Marchands

Le climat culturel à Montréal aux débuts de la société historique - Lajeunesse, Marcel (Montréal en tête, 2004)
Keywords: Bibliothèque Saint-Sulpice; Cabinet de lecture paroissial; Cercle Ville-Marie; Communautés religieuses; Oeuvre des bons livres; Sulpiciens

The Seed, the Soil, and the Climate: The Scottish Influence on Canadian Medical Education and Practice, 1775-1875 - Murray, Jock; Murray, Janet (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Médecine; Écossais

L'état de préparation des intervenants de l'Île de Montréal en l'an 2000 face à des pluies diluviennes comme celles du 14 juillet 1987 - Boissonneau, Julie (Université de Sherbrooke, 2001)
Keywords: Climat

Dynamics of Heavy Warm Season Precipitation Events in Montréal - Dookhie, Giselle C. (Université McGill, 2011)
Keywords: Climat

Planetary and Synoptic-Scale Analysis of Freezing Rain Events in Montreal, Quebec - Ressler, Gina (Université McGill, 2010)
Keywords: Climat

Accorder l’espace au temps - Torres, Juan; Lessard, Marie (Continuité, 2013)
Keywords: Climat

Effets du dioxyde d'azote et de l'ozone sur les maladies respiratoires à Montréal - Caouette, Chantal (Institut national de la recherche scientifique - Centre Eau Terre Environnement, 2010)
Keywords: Climat; Pollution

Étude de l'hivernité urbaine, analyse d'un récit de construction identitaire montréalais - Myriam, Guillemette (Université du Québec à Montréal, 2020)
Keywords: Carnaval; Climat; Espace souterrain

Montréal et son environnement naturel - Perron, Normand (Histoire de Montréal et de sa région, 2012)
Keywords: Climat; Géographie physique; Voie maritime

La réduction de gaz à effet de serre et les transports urbains des personnes à Montréal - Gandulfo, Mónica (Université de Sherbrooke, 2000)
Keywords: Automobile; Climat; Transport en commun

Montreal and Its Natural Environment - Perron, Normand (Montreal: The History of A North American City, 2018)
Keywords: Climat; Géographie physique; Voie maritime

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."--BOOK JACKET.
Keywords: Navigation

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale